A theory of incremental circle transform and its application for pose determination of two-dimensional objects - You, BJ; Bien, ZN; Lee, HY (ELSEVIER SCIENCE BV, 1999)
This paper describes a new pattern recognition method for locating objects based on a novel concept called incremental circle transform that effectively represents the shape of a boundary contour of an object as a vector function of incremental elements. The pose of an object is determined in a very fast manner independently of the position of an object and the starting point for boundary coding. (C) 1999 Elsevier Science B.V. All rights reserved.